The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/pssb.200301416
|View full text |Cite
|
Sign up to set email alerts
|

F centers in LiF: A nuclear magnetic resonance study

Abstract: PACS 61.82. Ms, 76.30.Mi, 76.60.Es Ionizing radiation like g-rays, electrons, or swift heavy ions create a variety of point defects in dielectric materials. The largest fraction of the defects consists of the paramagnetic F centers. Here, we study those F centers in LiF by nuclear magnetic resonance. Nuclear spin relaxation (T 1 ) measurements serve as a probe for the F centers offering the possibility to investigate their dynamics as a function of temperature and irradiation dose. Moreover, one is able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…4) yields activation energy of 0.13 eV ± 0.02 in the temperature range from 530 to 810 K. This value is close to activation energies for H center migration in LiF obtained by other authors [8,9]. In the case of F centers and their aggregates, the activation energy is known to be considerably higher (0.6-1.7 eV) [10,11]. The obtained result points to a possible role of interstitial halogen defects in the recovery processes.…”
Section: Resultssupporting
confidence: 80%
“…4) yields activation energy of 0.13 eV ± 0.02 in the temperature range from 530 to 810 K. This value is close to activation energies for H center migration in LiF obtained by other authors [8,9]. In the case of F centers and their aggregates, the activation energy is known to be considerably higher (0.6-1.7 eV) [10,11]. The obtained result points to a possible role of interstitial halogen defects in the recovery processes.…”
Section: Resultssupporting
confidence: 80%
“…Following HCP irradiation of single crystal LiF N Fmax is significantly greater. The many possible reasons for the enhanced production of vacancies/F centers following HCP irradiation are discussed elsewhere [1][2][3][4][5][6][7][8]38,42,[46][47][48][49][51][52][53]. In single crystal LiF following LID irradiation only the 5.08 eV and 4.77 eV OA bands are observed confirming that the 4.0 eV and 5.45 eV OA bands are dopant-related.…”
Section: Measurements Of Oa In Lifsupporting
confidence: 58%
“…In this range of levels of dose the F center dose response is sub-linear and proportional to D a (0.5 < a < 0.8) [51][52][53]. Other measurements on LiF:Mg,Ti samples were carried out without decomposition of the OA spectra [54].…”
Section: Optical Absorption Dose Response In Lifmentioning
confidence: 99%
“…Previously, feasibility of 7 Li FFC was demonstrated, but application was limited to a characterization of paramagnetic defects in a crystal [42]. We showed that 7 Li FFC provides straightforward access to the lithium ionic motion in a frequency range of 10 5 -10 9 s À 1 and, hence, in a time range of 10 À 9 -10 À 5 s. The lower limit of the frequency range results from the breakdown of conventional perturbation theory when the ZE interaction becomes weaker than the QP interaction, while the upper limit is determined by the available strength of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…While we will be able to exploit that 7 Li NMR STE experiments developed into a routine technique, we will have to establish 7 Li NMR FFC measurements as a new method for investigations of lithium ion dynamics in solids. Previously, the feasibility of 7 Li NMR FFC was demonstrated, but application was limited to an analysis of paramagnetic defects in LiF crystals [42]. The benefits of a combination of FFC and STE techniques will be shown for a (Li 2 S)-(P 2 S 5 ) glass.…”
Section: Introductionmentioning
confidence: 98%